Theoretical investigation of the physical properties of cubic perovskite oxides SrXO3 (X= Sc, Ge, Si). (May 2023) - Waqdim, A.; Agouri, M.; Abbassi, A.; Elhadadi, B.; Zidane, Z.; Taj, S.; Manaut, B.; Driouich, M.; El Idrissi, M.
Abstract: Various physical properties (electronic, optical and thermoelectric) of cubic perovskite oxides Sr X O 3 ( X = Sc, Ge, Si) are investigated by using the density functional theory (DFT) within Wien2K code. This code is based on different approximations such as generalized gradient approximation GGA, PBEsol, LDA, WC and the modified Becke–Johnson exchange potentials (mBJ, nmBJ and unmBJ). Structural properties and the optimization have been calculated using PBEsol functional which showed a significant results that are in good agreement with the experimental ones. The results for physical properties such as electronic, thermoelectric and optical are analyzed in detail by using the nmBJ approximation. The obtained results present an opening gap for SrSiO 3, SrGeO 3 and a metallic behavior for SrScO 3 . An average of transmittance which is about 94% to 97% was observed in the range of visible light. The increase of electrical conductivity with temperature confirms the effect of thermal agitation on the concentration of charges carriers using BolzTrap2 Package. Lastly a phonon dispersion was made and show that for X = Ge and Si, the structure is relatively stable while SrScO 3 is dynamically unstable. These results prove the ability that these materials can be exploited in many applications and manufacturing of optoelectronics for Sensors.